Spatial dynamics of soil nutrient in an age-graded poplar (Populus deltoides) plantation: Nutritional dynamics in Poplar plantations - Dhakad, Ashok Kumar (Indian Journal of Agroforestry, 2023)
Plantation age affects nutrient dynamics in soil depth and the growth of plantations. Hence, soil samples were analyzed at 0-15, 15-30, 30-60, and 60-90 cm depths under 1 to 7 years-old age-graded poplar plantations grown on sandy loam, silt loam, and loamy sand soils. Organic carbon and macro-nutrients increased progressively in all soils with subsequent increases in plantation age. Silt loam soil had higher carbon, N and K, whereas, P was higher in sandy loam. The increase in carbon, N, P and K were varied ~65-125%, ~27-130%, ~375-490% and ~47-135% due to integration of poplar for 7 years, of which maximum increase for carbon, N, P and K content was in loamy sand, sandy loam, and silt loam soils, respectively. A decreasing pattern was analyzed with increased soil depth. A sharp decline was observed in P in silt loam soil after 15 cm of soil depth. Surface soil had 2-3 times more carbon and macro-nutrients except for N (~0.5-0.8 time). Surface soil (0-15cm) showed sudden changes in soil texture and nutrients with soil depth. Thus, poplar being a deciduous tree and high influence on carbon and macro-nutrients with varying age, for improving soil productivity in low textured soil recommends without having any chemical amendments.